Phenolic Content, Antioxidant Properties, Key Enzyme Inhibitory Potential and Photoprotective Activity of Lawsonia inermis L. - Goudjil, Rima; Mekhaldi, Abdelkader; Benamar, Houari; Bensouici, Chawki; Kahoul, Mohamed A (Bentham Science Publishers, 2020)
Background: Lawsonia inermis Linn (Lythraceae), commonly known as “Henna” is a medicinal plant, which is widely used as a folk remedy and for its cosmetic properties. Objective: The objective of this present work was to evaluate biological activities and to quantify phenolics in extracts. Methods: The extracts were obtained from seeds of L. inermis by increasing the polarity of the solvent. The content of total phenolics, flavonoids, flavonols and tannins was determined using colorimetric methods. Also, to evaluate the antioxidant activity, six different assays, DPPH, ABTS, superoxide radical scavenging, inhibition of β-carotene bleaching, ferric reducing antioxidant power and phenanthroline assays were used. Enzyme inhibition activity was evaluated by acetylcholinesterase, butyrylcholinesterase and tyrosinase inhibition assays. Furthermore, photoprotective activity was determined by measuring sun protection factor. Results: The extraction efficiency of phenolics, as well as the biological activities of plant extracts, were affected by solvent polarity. The highest content of phenolics was determined in methanol extract (786.54 ± 0.00 mg GAEg-1 DW), followed by the aqueous and ethyl acetate extracts (526.48 ± 0.40 and 331.25 ± 0.00 GAEg-1 DW, respectively).The above extracts also exhibited the highest antioxidant activity, while low polar extracts were characterized with the lowest content of phenolics, as well as the lowest antioxidant capacity. The highest enzyme inhibition activities were found in ethyl acetate extract. Moreover, the methanol extract showed the best photoprotective activity with sun protection factor of 43.05 ± 0.37. Conclusion: These findings suggest a possible use of Henna seeds as a potential source of bioactive molecules with antioxidant, enzyme inhibition and skin protection properties.
Keywords: Lawsonia inermis, antioxidant activity, cholinesterase inhibition, tyrosinase inhibition, photoprotective activity, phenolic compounds.